Genus Lecanidion from India - A.M. Khole1, G.H. Balde2 and S.S. Bodke2, R.S. Deshmukh1*, R.R. Rakh2, S.M. Dalvi2 (Recent Research in Science and Technology, 2011)
The present paper deals with the taxonomic position of the genus Lecanidion Endl. and its distribution in India. The genus is at present represented by 9 species in India with the inclusion of 3 new species by authors viz. L. caesalpinae sp. nov., L. devigiriana sp. nov., and L. euphorbae sp. nov. Out of 9 species 6 species are reported from Maharashtra state.